The Widely Common Media to Teach English: Does YouTube Affect Students' Speaking Skills? - Hasyim, Nasihatul Ummah; Tarihoran, Naf'an (Indonesian Journal of English Language Studies (IJELS), 2024)
The digital age has brought about significant transformation in many aspects of life, including education. On top of that, Siemens and Downes (2020) argued that the current digital era is defined by a concept called connectivism. It suggested that learning is fundamentally a social and networked process. Thus, the theory provided a powerful perspective on how digital platforms such as YouTube have changed the learning space. In this study, the authors aimed to find out the proper answer about the effectiveness of YouTube as the media that is widely used by teachers in improving students’ English speaking skills. This study employed a qualitative systematic review. The authors set the criteria for selecting previous studies using Xiao and Watson’s (2019) framework. The criteria were as follows: (1) published in journals and available in Google Scholar, (2) within the last five years from 2019 – 2023, (3) specifically related to the effectiveness of using YouTube as learning media in EFL classrooms to enhance students’ speaking skills, and (4) original research article and using a quantitative approach. As a whole, this study supported the notion that integrating YouTube into the language classroom can lead to significant improvements in students’ speaking skills, ultimately contributing to their overall language proficiency and motivation.